An Assessment of Long-Term Opioid Use Following Tibial Plateau Fracture Repair: An At-Risk Patient Population Based on Race/Ethnicity. Issue 3 (July 2019) - Radi, Joshua K.; Curtis, Amy B.; DiSilvio, Frank; Vangsnes, Eric; Byram, Scott; Summers, Hobie
Abstract : Objectives: Is there a difference in percentage of opioid use at 3 and 6 months among different races/ethnicities following tibial plateau fracture repair after controlling for potential confounders? Methods: Retrospective secondary data analysis of 18- to 65-year-old patients with operative tibial plateau fractures between 2006 and 2015 at a level-I trauma center. Exclusion criteria included preinjury opioid use or history of opioid dependence, American Society of Anesthesiologists class ≥3, renal or lower extremity neurological impairment, and/or rheumatoid arthritis. Three hundred fifteen operative tibial plateau fractures were identified and, following application of our exclusion criteria, final sample size was 211. Intervention included single-shot peripheral nerve block (PNB) vs. no PNB. Main outcome measurements were opioid use at 3 or 6 months compared among all race/ethnicities. Results: Black patients were less likely to be on prescription opioids than whites at both 3 months (p = 0.015, odds ratio [OR] = 0.396 [0.188 to 0.835]) and 6 months (p = 0.027, OR = 0.239 [0.067 to 0.852]). Hispanic patients did not differ statistically from white patients in having an opioid prescription at 3 or 6 months. Smokers were independently more likely to be on prescription opioids than nonsmokers at 6 months (p = 0.013, OR = 2.874 [1.245 to 6.635]). Conclusions: Disparities exist with regard to opioid use among white and black patients following lower extremity surgery, regardless of PNB status. White patients are at risk for long-term opioid use following tibial plateau fracture repair and black patients may not be receiving adequate pain control postoperatively. Smoking was found to be associated with long-term opioid use.